The influence of nutrition on periodontal health: Literature review (Research, Society and Development, 2025)
Periodontal disease is a chronic inflammatory condition of multifactorial origin, associated with bacterial biofilm, that affects the supporting tissues of the teeth and can lead to tooth loss. Among the factors influencing its progression, nutritional aspects stand out, as an inadequate diet can intensify the inflammatory response and worsen the clinical condition of the disease. Thus, the present study aimed to analyze the influence of nutritional factors on periodontal health, covering both structural changes and clinical aspects. A narrative literature review was conducted, including documents published between 2013 and 2025, in Portuguese and/or English, using the following databases: PubMed, Scientific Library Electronic Online (SciELO), Research, Society and Development, Google Scholar, and books. The analysis revealed that nutrients such as vitamin C, vitamin D, and omega-3 fatty acids have beneficial effects on periodontal health, while diets rich in refined sugars and fats can worsen the condition. It was concluded that adopting a balanced diet rich in specific nutrients can prevent and control periodontal diseases, being essential for both oral and overall health.